Development of E-Teaching Materials for Science on the Topic of the Form of Matter and Its Changes Integrated with Ethnoscience with the Help of Augmented Reality to Improve the Learning Outcomes of Elementary School Students - Fatza Hermayanti; Ani Rusilowati (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop, test the feasibility, practicality, and effectiveness of e-teaching materials integrated with ethnoscience assisted by Augmented Reality (AR) in improving student learning outcomes. The type of research used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The results of the study indicate that the developed e-teaching materials are declared very feasible based on validation by material, language, and media experts with an average score of 89%. The practicality of the media is demonstrated through the responses of teachers and students who are in the very positive category, with a percentage of 97% of teachers and 86% of students. The effectiveness of e-teaching materials is proven through the results of the paired sample t-test which shows a significance value of 0.000 (<0.05), which means there is a significant difference between learning outcomes before and after using the media. In addition, the results of the N-Gain test of 0.67 indicate a moderate category, which indicates an increase in student learning outcomes. Thus, the integrated ethnoscience e-teaching materials assisted by Augmented Reality are declared feasible, practical, and effective for use in science learning for grade IV elementary schools, especially on the material of states of matter and their changes